Single‐Cell Analysis of Cytokine mRNA and Protein Expression by Flow Cytometry. Issue 1 (24th February 2020) - Pal, Rubina; Schaubhut, Jayne; Clark, Darcey; Brown, Lynette; Stewart, Jennifer J.
Abstract: Understanding how immune cells respond to external stimuli such as pathogens or drugs is a key component of biomedical research. Critical to the immune response are the expression of cell‐surface receptors and the secretion of cytokines, which are tightly regulated by gene expression and protein synthesis. Previously, cytokine mRNA expression levels have been measured from bulk analysis of heterogeneous or sorted cell populations, and the correlation between cytokine mRNA expression and protein levels using these techniques can be highly variable. Flow cytometry is used to monitor changes in cell‐surface and intracellular proteins, but some proteins such as cytokines may be transient and difficult to measure. Thus, a flow cytometry method that can simultaneously measure cytokine mRNA and protein levels in single cells is a very powerful tool. We defined a flow cytometry method that combines the conventional measurement of T cell surface proteins (CD45, CD3, CD4, CD8) and intracellular cytokines (IL‐2, INF‐γ) with fluorescent in situ hybridization and branched DNA technology for amplification and detection of IL‐2 and INF‐γ mRNA transcripts in activated T cells. This method has been applied to frozen peripheral mononuclear blood cells (PBMCs) and frozen blood samples, making it applicable to clinical trial specimens that require shipment to the test site. In CD4 + cells from activated PBMCs, the concordance between mRNA and protein levels was 41% for IL‐2 and 21% for and INF‐γ. In CD8 + cells from activated PBMCs, the concordance was 15% for IL‐2 and 32% for INF‐γ. © 2020 by John Wiley & Sons, Inc. Basic Protocol : Detection of IL‐2 and IFN‐γ mRNA and protein expression in frozen PBMCs Alternate Protocol : Detection of IL‐2 and IFN‐γ mRNA and protein expression in frozen blood